2021
DOI: 10.3390/jcm10245841
|View full text |Cite
|
Sign up to set email alerts
|

Skin Manifestations in Psoriatic and HS Patients in Treatment with Biologicals during the COVID-19 Pandemic

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic, a global public health emergency, has changed dermatology practice and daily routine in just under two years. Much has been written in the literature about COVID-19-associated skin manifestations. Nevertheless, much less has been written regarding skin manifestations in patients affected by severe immune-mediated skin diseases, e.g., psoriasis and hidradenitis suppurativa, undergoing biological treatment during the COVID-19 outbreak. Thus, the aim of this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
0
0
0
Order By: Relevance
“…Te COVID-19 infection's impact on the worsening efect of psoriasis remains a hot topic. Previous research suggested that no adherence to the biologics was related to the psoriasis fare-up [22]. Although the infection of SARS-CoV-2 might play a crucial direct role in psoriasis aggravation, the pieces of literature about it were mainly presented as cases.…”
Section: Discussionmentioning
confidence: 99%
“…Te COVID-19 infection's impact on the worsening efect of psoriasis remains a hot topic. Previous research suggested that no adherence to the biologics was related to the psoriasis fare-up [22]. Although the infection of SARS-CoV-2 might play a crucial direct role in psoriasis aggravation, the pieces of literature about it were mainly presented as cases.…”
Section: Discussionmentioning
confidence: 99%